THE RISE OF CONSCIOUSNESS IN MODERN HINDI LITERATURE: THE UNDERCURRENTS OF SOCIETY AND LITERATURE - Singh, Mahendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The “stream of consciousness” in literature is a specific narrative technique whose main purpose is to depict the internal processes of a character’s mind by presenting his thoughts and feelings in a continuous, usually disjointed and non-linear manner. This technique was first introduced in literature by writers like James Joyce, Virginia Woolf and William Faulkner, and it sees widespread use in today’s literature. In this blog post, we will discuss in detail the stream of consciousness technique and ways to use it effectively in literature.